CROSS CULTURAL UNDERSTANDING LEARNING METHOD - Titim Eliawati (Universitas Potensi Utama, 2019)
Cross cultural understanding is one of the courses that require lecturers' creativity in their teaching in the classroom. Students difficulties in understanding cross cultural until they can feel the cultural confusion experienced by a stranger who enters a region that has a different culture with him/ her. The purpose of this study is to get the best method used in course learning cross cultural understanding. The method used is research literature by comparing and analyzing some cross-cultural understanding of learning methods in several past studies. The results of this study are 1) The used learning method must involve students in the foreign culture studied; 2) Internet is one of the best learning media in the process of learning cross cultural understanding; 3) Students at least understand the language of the culture studied. The conclusion of this study is that cross cultural understanding learning is not easy to do if it only provides theory because students need an in-depth understanding of the cross-cultural process which experienced by someone.